2021
DOI: 10.3390/ma14174859
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Methylcellulose Based Polymer Electrolyte Impregnated with Potassium Ion Conducting Carrier: Impedance, EEC Modeling, FTIR, Dielectric, and Device Characteristics

Abstract: In this research, a biopolymer-based electrolyte system involving methylcellulose (MC) as a host polymeric material and potassium iodide (KI) salt as the ionic source was prepared by solution cast technique. The electrolyte with the highest conductivity was used for device application of electrochemical double-layer capacitor (EDLC) with high specific capacitance. The electrical, structural, and electrochemical characteristics of the electrolyte systems were investigated using various techniques. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 65 publications
(89 reference statements)
0
18
1
Order By: Relevance
“…The fitting parameters for the EEC and DC conductivity values are listed in Table 1 and Table 2 , respectively. The R b is calculated by intercepting the real and spike axes [ 60 ]. Figure 2 shows polymer electrolyte structure and proposed ion conduction mechanism in the PVA:MC:NH 4 I electrolyte system.…”
Section: Resultsmentioning
confidence: 99%
“…The fitting parameters for the EEC and DC conductivity values are listed in Table 1 and Table 2 , respectively. The R b is calculated by intercepting the real and spike axes [ 60 ]. Figure 2 shows polymer electrolyte structure and proposed ion conduction mechanism in the PVA:MC:NH 4 I electrolyte system.…”
Section: Resultsmentioning
confidence: 99%
“…To examine dipole relaxation in polymeric materials, dielectric relaxation spectroscopy was accomplished over a large frequency range [ 29 ]. Using the following equations, the real and imaginary parts of ε * and M * may be calculated from the real ( Z ′) and imaginary ( Z ″) parts of Z * [ 9 , 30 , 31 ]: …”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that a low-density dielectric material configuration correlates to a low-density component [ 4 ]. Previous studies demonstrated that salt added into polymers such as chitosan, methylcellulose, dextran, polyethylene oxide, and polyvinyl alcohol are crucial to reducing the resistivity of polar polymers and increasing the DC conductivity owing to salt dissociation by the host polymer functional groups [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Herein, the material of use is PVC host polymer that experiences several different behaviors, making it remarkably different from that previously reported for polymer electrolyte (PEs) materials.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, PEs appear as materials of interest that possess the required conductivity, as well as electrochemical stability [ 1 , 2 , 3 ]. For example, dimensional stability, durability, a relatively wide potential window (usually above 1.5 V), and its eco-friendly nature are all properties of these materials [ 4 ]. The characterizations of PEs are highly required because of its utilization in multidisciplinary fields, such as electrochemistry, polymer science, organic chemistry, and inorganic chemistry [ 5 ].…”
Section: Introductionmentioning
confidence: 99%